Corporate Reputational Dynamics and Their Impact on Global Commodity Markets - Li, Iris; Akyildirim, E; Conlon, T; Corbet, S (Elsevier BV, 2025)
This research examines investor response to negative Environmental, Social, and Governance (ESG) reputational events across international commodity-related corporations. By distinguishing between G7 and non-G7 nations, we highlight a negative equity market response to such ESG-related reputational events, emphasising the influence of regional, governance and environmental factors alongside corporate reporting practices. The research further assesses the potential of corporate ESG preparedness in mitigating negative market outcomes. It also identifies commodities such as wheat, rice, and cocoa to be notably susceptible to reputational dynamics, whereas commodity markets such as oil and gold present evidence of marked resilience. The findings emphasise the importance of sector-specific regulatory approaches to ensure rigorous governance standards, especially in essential food production sectors.
Keywords: 3502 Banking, Finance and Investment; 35 Commerce, Management, Tourism and Services; 16 Peace, Justice and Strong Institutions; 1402 Applied Economics; 3502 Banking, finance and investment; 3801 Applied economics; ESGCSR, Commodity markets, Reputational disaster, Investor response